Influence of the scattering of flax fibres properties on flax/epoxy woven ply stiffness. (15th May 2017) - Scida, Daniel; Bourmaud, Alain; Baley, Christophe
Abstract: The natural character of plant fibres was often cited as a disadvantage which results in the scattering of their properties. This work aims at studying the influence of this scattering on the stiffness of an epoxy-flax fibres twill fabric ply. Elastic coefficients were estimated using an analytical model in an elliptical configuration based on the use of the classical laminate theory. Most of flax fibre elastic coefficients were obtained in the literature; in addition, a flax fibre Poisson's ratio of 0.498 was estimated from an experimentally inverse approach. Then, the use of the analytical model evidenced that the Young's moduli of woven composite were strongly correlated to longitudinal and transversal fibre ones; moreover, the fibre transversal modulus had a significant impact on the Poisson's ratios of the composite. As regards to the yarn configuration and architecture, we showed that the mean twisting angle significantly affected stiffness and Poisson's ratio of the composite; in the same way, the importance of waviness described by its waviness ratio was underlined whereas the scattering into yarn morphology had low influence on composite performances when the waviness ratio was high. Graphical abstract: Highlights: We studied the influence of the fibre properties scattering on the stiffness of an epoxy-flax fibres twill fabric ply. An analytical model, based on the thin laminate theory on the woven structure, was validated in an elliptical configuration. A Poisson's ratio of flax fibre of 0.498 was estimated from an experimentally inverse approach. The Young's moduli of woven composite were strongly correlated to longitudinal and transversal fibre ones. The mean twisting angle significantly lowered the E x and ν xz values whereas it increased the G xy and ν xy values.